RELASI INTELEKTUALITAS DAN SPIRITUALITAS DALAM BERAPOLOGETIKA: SUATU TINJAUAN INJILI - Nathanail Sitepu (Sekolah Tinggi Teologi Ekumene Jakarta., 2020)
This article highlights the opinion which states that apologetic activities are activities that only hone intellectually but have no impact on one's spirituality or spirituality. As a result, the argument is that apologetic activities currently rife on social media only end in debating with coaches or attacking and humiliating one another. Often what stands out is sectarian egoism, not love for winning souls to Christ. The method used is a literature research approach, then analyzed with a comparative analytical approach in assessing apologetic activities related to intellectuality and spirituality. The study of this article reveals that Apologetics is closely related to the development of one's intellect and spirituality. The failure by some apologists to show the maturity of their spirituality in debate, does not necessarily become the final measure that apologetics does not bring people closer to God. The conclusion that is found is that there is a strong correlation for the development of intellectuality and spirituality when someone is apologetic. This is because apologetics encourages a person to study the Scriptures and learn to understand, pronounce, and do it.